Forest Rotations and Stand Interdependency: Ownership Structure and Timing of Decisions - Gregory S. Amacher; Erkki Koskela; Markku Ollikainen (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper extends the Hartman model to study the optimal rotation age of two interdependent stands when the stream of amenities produces from the two stands may be complements or substitutes, both in space and over time. In the presence of stand interdependence both the ownership structure and the sequence of decision making matters. Rotation age choices are examined and compared under a variety of equilibria, including Nash, Stackelberg, and sole owner cases which differ as to the level of commitment by landowners to their choices. We show that the sole owner's rotation age is longer than the rotation age solved under both Nash and Stackelberg assumptions if the stands are spatial complements, but shorter if they are substitutes. The precise relationship between the Nash and Stackelberg rotation ages, and the qualitative properties of rotation ages in terms of timber prices, regeneration costs, and interest rates, also depend on how spatial substitutability and complementarity between stands evolves through time.
Keywords: 330; forest rotation; amenity services; stand interdependence